Novel Mouse Models of Methylmalonic Aciduria Recapitulate Phenotypic Traits with a Genetic Dosage Effect - Forny, Patrick (J Biol Chem, 2016)
Methylmalonic aciduria (MMAuria), caused by deficiency of methylmalonyl-CoA mutase (MUT), usually presents in the newborn period with failure to thrive and metabolic crisis leading to coma or even death. Survivors remain at risk of metabolic decompensations and severe long term complications, notably renal failure and neurological impairment. We generated clinically relevant mouse models of MMAuria using a constitutive Mut knock-in (KI) allele based on the p.Met700Lys patient mutation, used homozygously (KI/KI) or combined with a knockout allele (KO/KI), to study biochemical and clinical MMAuria disease aspects. Transgenic Mut(ki/ki) and Mut(ko/ki) mice survive post-weaning, show failure to thrive, and show increased methylmalonic acid, propionylcarnitine, odd chain fatty acids, and sphingoid bases, a new potential biomarker of MMAuria. Consistent with genetic dosage, Mut(ko/ki) mice have lower Mut activity, are smaller, and show higher metabolite levels than Mut(ki/ki) mice. Further, Mut(ko/ki) mice exhibit manifestations of kidney and brain damage, including increased plasma urea, impaired diuresis, elevated biomarkers, and changes in brain weight. On a high protein diet, mutant mice display disease exacerbation, including elevated blood ammonia, and catastrophic weight loss, which, in Mut(ki/ki) mice, is rescued by hydroxocobalamin treatment. This study expands knowledge of MMAuria, introduces the discovery of new biomarkers, and constitutes the first in vivo proof of principle of cobalamin treatment in mut-type MMAuria.